2015
DOI: 10.3389/fmars.2015.00007
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of invasive lionfish (Pterois spp.)

Abstract: Indo-Pacific lionfishes, Pterois volitans (Linnaeus, 1758) and Pterois miles (Bennett, 1828), native to the Pacific and Indian Oceans, respectively, were first observed in the western Atlantic off Florida in 1985. They have since spread and are established throughout the broader Caribbean region. Despite potentially devastating ecological and economic effects, information on key life history characteristics for lionfish in the invaded range is sparse. Objectives of this study were to quantify (1) periodicity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 32 publications
4
49
0
7
Order By: Relevance
“…Juvenile lionfish are an understudied life stage in terms of individual impact upon prey populations. The conclusions from this data are limited to juveniles under experimental conditions, however, due to high lionfish fecunidity (Gardner et al 2015) and low efficacy of juvenile removal by divers (Barbour et al 2011;Morris et al 2011) they should be considered a pervasive threat to crustacean prey populations.…”
Section: Discussionmentioning
confidence: 90%
“…Juvenile lionfish are an understudied life stage in terms of individual impact upon prey populations. The conclusions from this data are limited to juveniles under experimental conditions, however, due to high lionfish fecunidity (Gardner et al 2015) and low efficacy of juvenile removal by divers (Barbour et al 2011;Morris et al 2011) they should be considered a pervasive threat to crustacean prey populations.…”
Section: Discussionmentioning
confidence: 90%
“…Prey naïveté in the invaded range, along with the lionfishes' resemblance to more benign organisms, also appears to contribute to their hunting success (Cure et al 2012). Considering these feeding characteristics, their rapid growth rate (Edwards et al 2014), small size-at-maturity (Morris 2009, Gardner et al 2015, high fecundity and high spawning frequency (Morris 2009, Gardner et al 2015, and apparent lack of natural predators (Albins & Hixon 2013), there is great concern that if their populations are not properly managed, invasive lionfish could cause significant ecological disruption in Bermuda, through predation and resource competition. Elsewhere, Albins & Hixon (2008) showed that lionfish can reduce the recruitment of reef fish by nearly 80% in as little as 5 wk.…”
Section: Introductionmentioning
confidence: 99%
“…Claydon et al (2012), estimaron que el 71 % de los peces que se encontraban en los hábitats de poca profundidad tenían menos de un año. Para Xcalak a partir del 2011, se presentó mayor porcentaje de organismos con edades superiores al año, es decir tallas de aproximadamente 190 mm de Lt, las cuales corresponden a organismos reproductores (Gardner et al, 2015).…”
Section: Discussionunclassified
“…Además de representar una invasión rápida (Ruttenberg et al, 2012), según Sutherland et al (2010), la considera entre los problemas que más afectan la conservación de la diversidad biológica en el Caribe. Esta especie alcanza mayores tallas y densidades poblacionales en sus nuevas áreas, que en las nativas debido a su alta tasa reproductiva (Gardner et al, 2015), a la ausencia de depredadores (Darling et al, 2011), a su habilidad competitiva con especies nativas (Albins, 2013) y al apetito voraz, siendo un consumidor generalista (Valdez-Moreno, Quintal-Lizama, Gómez-Lozano, & García-Rivas, 2012). Los impactos derivados de su presencia en los arrecifes del Atlántico van desde la reducción en el reclutamiento de peces hasta un 79 % y una disminución en la biomasa de 65 % (Albins & Hixon, 2008;Green, Akins, Maljković, & Côté, 2012).…”
unclassified